Curative Effect of AD-MSCs against Cisplatin-Induced Hepatotoxicity in Rats is Potentiated by Azilsartan: Targeting Oxidative Stress, MAPK, and Apoptosis Signaling Pathways - Amany Abdlrehim Bekhit; Olivia N. Beshay; Michael A. Fawzy; Sara Mohamed Naguib Abdel-Hafez; Gaber El-Saber Batiha; Farid S. Ataya; Moustafa Fathy (Stem Cells International)
Despite its clinical value, cisplatin (CISP) is complicated by marked hepatotoxicity via inducing oxidative stress, inflammatory, and apoptotic pathways. This study aims to explore the protective impact of azilsartan (AZIL), an antihypertensive drug, in addition to adipose tissue-derived mesenchymal stem cells (AD-MSCs) on CISP-induced hepatotoxicity. After characterization and labeling of AD-MSCs by PKH26 dye, 54 Wistar male albino rats were randomly divided into nine groups: I (CONT), II (AZIL.H), III (CISP), IV (CISP + AZIL.L), V (CISP + AZIL.H), VI (CISP + AD-MSCs), VII (CISP + AZIL.L + AD-MSCs), VIII (CISP + AZIL.H + AD-MSCs), and IX (CISP + VITA C). Serum alanine aminotransferase (ALT), alanine aminotransferase (AST), and albumin levels were determined. Assessment of reactive oxygen species, malondialdehyde, and glutathione contents, and superoxide dismutase activity and histopathological evaluations were done on hepatic tissue. Quantitative real-time PCR was utilized to estimate the expression of TNF-α and IL-6 genes. Cell homing of labeled AD-MSCs to the liver tissues was investigated. Hepatic expression of JNK1/2, ERK1/2, p38, Bax, Bcl-2, and cleaved caspase-3 proteins was investigated by western blot analysis. CISP elevated serum ALT and AST activities, reduced albumin level, and remarkably changed the hepatic architecture. It increased the expression TNF-α and IL-6 genes, raised the expression of JNK1/2, ERK1/2, p38, Bax, and cleaved caspase-3 proteins, and diminished the Bcl-2 protein. By contrast, treatment of animals with either AZIL or AD-MSCs dramatically reduced the effects of CISP injection. Moreover, treatment with combination therapy (AZIL.L or H + AD-MSCs) considerably mitigated all previously mentioned alterations superior to AZIL or AD-MSCs alone, which might be attributed to the AZIL-enhanced homing ability of AD-MSCs into the injured liver tissue. In conclusion, the present findings demonstrated that AZIL improves the hepatoprotective potential of AD-MSCs against CISP-induced hepatotoxicity by modulating oxidative stress, mitogen-activated protein kinase, and apoptotic pathways.